Optimal policy analysis in a macro-focused union : a quantitative assessment - Sinthavy, Anoulat (2016)
There is very little theoretical study that focuses on “Macro-based” union. In an economy with “Macro-focused” union, what is the optimal level of taxation rate and union member fee such that the social welfare is maximized? To address these questions, we develop a tractable general equilibrium framework that is suitable to study a “Macro-based” union. Our model mimics various facts such as union members are offered an endogenously determined goods discount rate, taxation exemption for union firms and individuals hold heterogeneous preference against union. Union size, price of union and non-union goods, number of union and non-union firms are all endogenously determined in the model. Quantitative analysis shows that different levels of taxation rate and union member fee affect social welfare and various economic parameters differently. Results suggest that lowering taxation rate on non-union firms is overall beneficial and the optimal union membership fee is zero when individuals do not have strong preference over non-union goods and in the presence of taxation policy.